Variation along drying of the textural properties of pears. - Barroca, Maria João (2013)
Texture results from complex interactions between the different food components, and the changes in texture that occur during the processing of foods have been related to tissue and cell microstructural changes [1]. The textural properties, as well as appearance and flavour, are the most influencing organoleptic quality attributes which establish the acceptability of foods by the consumers. Therefore, there has been a large interest in developing methods to predict and control the texture of foods, particularly in relation to processing treatments, such as drying. Instrumental texture profile analysis (TPA) is one of the methods to determine the texture by simulating or imitating the repeated biting or chewing of a food. The pears used in the present study are of the same variety which is traditionally dried in Portugal (S. Bartolomeu), and they were purchased to a traditional producer of dried pears. The traditional drying method consists of an open-air sun exposure procedure, and to avoid all the inconveniences of such a process, like product hygienic security and adverse climatic conditions, alternative drying technologies are being tested. In the present work, the pears were dried in two different systems having also the sun as the energy source: a solar stove (ESAV) and a solar drier (ESTV). The drying was stopped at a moisture content of about 20 %. Along the drying process samples were used from both drying systems to evaluate their texture. The texture profile analysis to all the samples was performed using a Texture Analyser, and the textural properties: hardness, adhesiveness, springiness, cohesiveness, and chewiness were then calculated after standard equations. The objective of this work is, on one hand, to evaluate how the textural attributes change along time during the drying operation and, on the other hand, to compare the two drying methods used. From the results obtained is possible to see that the drying operation greatly affects the textural properties of the pears, so that the hardness diminishes very much along drying, for both the drying systems tested, as seen in Figure 1. Figure 1 also shows that the drying is quite faster in the solar drier (ESTV) than in the solar stove (ESAV), taking about 50 hours to reach the desirable moisture content of about 20 % (wet basis), whereas the solar stove takes about 90 hours to reach the same moisture content.